Impact of psychological stress resulting from competition on probability of sports injuries among athletes - Hamidi, Ali Khayon Tarish; Hegel, Saif Salah Hassan (Universitas Tanjungpura, 2026)
Background. Sports competitions are significant psychological stress factors for athletes, increasing the risk of sports injuries. Exposure to psychological stressors during sports competitions like fear of failure, fear of being evaluated by others, excessive excitation from a high degree of responsibility for performance, can cause attention disruption and disturbance of the athlete’s psychomotor skill performance. As a result, there is an increased risk of injury during sports competitions. Objectives. This research aims to study relationship between levels of psychological stress during competition and probability of athletes sustaining injuries. Methods. The correlational research design was conducted with young athletes involved in individual sports and team sports. The subjects of this study were all athletes affiliated with Iraqi clubs, schools, and universities who compete in national, regional, and local competitions—approximately 50 to 100 male and female athletes. Structured questionnaires were utilized to collect data on psychological variables: competition anxiety, psychological stress level, fear of failure, and probability of sports injuries. Descriptive statistics (Mean, SD, CV) were calculated for demographic data, psychological variables and Pearson correlation analysis was performed. Results. A moderate positive correlation between psychological anxiety and probability of sports injuries was found (r = 0.68; p = 0.001), indicating that as psychological anxiety increases so does the probability of sports injuries. There was a moderate positive correlation between psychological stress level and probability of sports injuries (r = 0.65; p = 0.002), suggesting that as psychological stress level increase so does the probability of sports injuries. There was a strong positive correlation between fear of failure and probability of sports injuries (r = 0.70; p = 0.001), suggesting that as fear of failure increases so does the probability of sports injuries. Conclusion. This study concluded that psychological stress during sports competitions had a correlation with sports injuries. This study adds to the body of knowledge by showing how psychological preparation should be taken seriously and implemented during athletes’ training to avoid sports injuries.